2014
DOI: 10.1093/intimm/dxu069
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin rCRAMP stimulates rat mast cells to generate cysteinyl leukotrienes, synthesize TNF and migrate: involvement of PLC/A2, PI3K and MAPK signaling pathways

Abstract: Cathelicidins represent a family of cationic peptides involved in host defense systems. Apart from exerting direct anti-microbial effects, cathelicidins can regulate immune responses by affecting the activity of cells playing a role in antibacterial defense. Taking into account that mast cells are critical components of host defense, the aim of this study was to determine whether rat cathelicidin-related anti-microbial peptide (rCRAMP) can influence mast cell activity. We have demonstrated that activation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Previously reported findings also showed that mice deficient in MyD88 and IRAK-4 are highly susceptible to Staphylococcus aureus infection and succumb to infection, demonstrating the in vivo significance of MyD88 and IRAK-4 in pathogen-induced immune responses (32,57). MAPK pathways are involved in the modulation of CRAMP expression (38). The level of p38 MAPK was increased in M. bovis BCG-infected BM-MSCs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previously reported findings also showed that mice deficient in MyD88 and IRAK-4 are highly susceptible to Staphylococcus aureus infection and succumb to infection, demonstrating the in vivo significance of MyD88 and IRAK-4 in pathogen-induced immune responses (32,57). MAPK pathways are involved in the modulation of CRAMP expression (38). The level of p38 MAPK was increased in M. bovis BCG-infected BM-MSCs.…”
Section: Discussionmentioning
confidence: 72%
“…The MyD88-TLR interaction is known to recruit members of the IRAK family and initiates signaling through MAPK pathways (37). Moreover, previous studies showed that MAPK pathways are involved in the modulation of CRAMP expression (38). In order to identify the MAPK pathway that could be involved in the regulation of Camp expression, we checked the expression of MAPK proteins in M. bovis BCG-infected BM-MSCs.…”
Section: Upregulation Of Camp By Tlrs Is Mediated Via Myd88 and Il-1 mentioning
confidence: 99%
“…Cathelicidin LL-37 promotes degranulation and preformed mediator release from human lung mast cells [ 61 ] and stimulates degranulation and Ca 2+ mobilization in immature LAD2 human mast cells [ 62 , 63 ] as well. Moreover, this peptide activates LAD2 mast cells to synthesis and releases the strong pro-inflammatory mediators such as LTC 4 and PGD 2 [ 64 ] and rat CRAMP stimulates mature mast cells to production and release cysteinyl (cys)LTs [ 65 ]. Importantly, anti-inflammatory cytokine IL-10, but not TNF, IL-6 and CCL5, strongly inhibits CRAMP-induced cysLT synthesis [ 65 ].…”
Section: Cathelicidins Affect Mast Cell Activitymentioning
confidence: 99%
“…Moreover, this peptide activates LAD2 mast cells to synthesis and releases the strong pro-inflammatory mediators such as LTC 4 and PGD 2 [ 64 ] and rat CRAMP stimulates mature mast cells to production and release cysteinyl (cys)LTs [ 65 ]. Importantly, anti-inflammatory cytokine IL-10, but not TNF, IL-6 and CCL5, strongly inhibits CRAMP-induced cysLT synthesis [ 65 ]. Moreover, LL-37 activates mast cells to produce newly generated cytokines, including IL-2, IL-4, IL-6, IL-31, GM-CSF, and TNF, and chemokines CCL4 and CXCL8 [ 60 , 63 , 64 ].…”
Section: Cathelicidins Affect Mast Cell Activitymentioning
confidence: 99%
“…There are several signaling molecules reported to be involved in MC differentiation, including janus kinase (JAK), signal transducer and activator of transcription (STAT), Lck/Yes novel tyrosine kinase (Lyn), Spleen tyrosine kinase (Syk), linker for activation of T cell (LAT), Fyn, GRB2-associated-binding protein 2 (Gab2), Ras, Raf, and MEK [21][22][23][24][25][26][27][28][29][30][31]. These molecules play crucial roles in either PI3K or MAPK signaling [28][29][30] (Fig.…”
Section: Wortmannin a Pi3k Inhibitor Significantly Abrogated The Inmentioning
confidence: 99%